Efficient conditioned pain modulation despite pain persistence in painful diabetic neuropathy - Granovsky, Yelena (Pain Rep, 2017)
INTRODUCTION: Alleviation of pain, by either medical or surgical therapy, is accompanied by transition from less efficient, or pro-nociceptive, to efficient conditioned pain modulation (CPM). Spontaneous decrease or resolution of pain with disease progression is reported for some patients with painful diabetic neuropathy (PDN). OBJECTIVES: To explore whether CPM changes similarly in parallel to spontaneous resolution of pain in PDN patients. METHODS: In this cross-sectional study, thirty-three patients with PDN underwent psychophysical assessment of pain modulation on the forearm, remote from the clinical pain. RESULTS: Pain duration was not correlated with neuropathic pain intensity, yet, it correlated with CPM efficiency; patients with longer pain duration had same pain level, but more efficient CPM than those with short-pain duration (ρ = −0.417; P = 0.025, Spearman correlation). Patients with pain more than 2 years (median split) expressed efficient CPM that was not different from that of healthy controls. These patients also had lower temporal summation of pain than the short-pain duration patients group (P < 0.05). The 2 patient groups did not differ in clinical pain characteristics or use of analgesics. CONCLUSION: Pro-nociception, expressed by less efficient CPM and high temporal summation that usually accompanies clinical painful conditions, seems to “normalize” with chronicity of the pain syndrome. This is despite continuing pain, suggesting that pro-nociceptivity in pain syndromes is multifactorial. Because the pain modulation profile affects success of therapy, this suggests that different drugs might express different efficacy pending on duration of the pain in patients with PDN.